Can Mentoring Help Female Assistant Professors? Interim Results from a Randomized Trial - Blau, Francine D; Currie, Janet M; Croson, Rachel T. A; Ginther, Donna K (American Economic Review, 2010)
Can Mentoring Help Female Assistant Professors? Interim Results from a Randomized Trial by Francine D. Blau, Janet M. Currie, Rachel T. A. Croson and Donna K. Ginther. Published in volume 100, issue 2, pages 348-52 of American Economic Review, May 2010